Selling luxury watches in Asia: the changing position of independent distributors - Pierre-Yves Donzé; Thierry Theurillat (Marketing Review St.Gallen, 2016)
Asia has increasingly become the place to sell luxury goods as a result of economic growth. Swiss luxury watch groups have all turned to new Asian markets since the late 1990s, with the help of key intermediaries such as local distributors and retailers. However, facing the verticalization strategies of large groups to improve the control and even to develop in-house retail management, independent distributors have needed to change their business models and offer new kinds of services to access customers. This article gives two examples of local independent distributors' new strategies to cope with verticalization by large groups. While the first company, The Hour Glass, turned to mono- and multi-brand stores for independent luxury brands in South East Asia, the second one, Hengdeli, specialized in retail by running in-house shops for the market expansion in China of one of its main partners, Swatch Group.
Keywords: 650